The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41398-021-01770-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lisdexamfetamine dimesylate on eating behaviour and homeostatic, reward and cognitive processes in women with binge-eating symptoms: an experimental medicine study

Abstract: Lisdexamfetamine dimesylate (LDX) is the only drug currently approved by the FDA for the treatment of Binge-Eating Disorder (BED), but little is known about the behavioural mechanisms that underpin the efficacy of LDX in treating BED. We examined the behavioural and neural effects of an acute dose of LDX (50 mg) in 22 women with binge-eating symptomatology using a randomised, crossover, double-blind, placebo-controlled experimental medicine design. LDX reduced self-reported appetite ratings and intake of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Likewise, reductions in vmPFC correlated with reductions in binge eating behaviors. Other studies have associated lisdexamfetamine with reduced activity bilaterally in the thalamus in individuals with BED when viewing food pictures [ 138 ]. Likewise, lisdexamfetamine appears to reduce motor impulsivity, but does not appear to have an effect on working memory or emotional bias [ 138 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, reductions in vmPFC correlated with reductions in binge eating behaviors. Other studies have associated lisdexamfetamine with reduced activity bilaterally in the thalamus in individuals with BED when viewing food pictures [ 138 ]. Likewise, lisdexamfetamine appears to reduce motor impulsivity, but does not appear to have an effect on working memory or emotional bias [ 138 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have associated lisdexamfetamine with reduced activity bilaterally in the thalamus in individuals with BED when viewing food pictures [ 138 ]. Likewise, lisdexamfetamine appears to reduce motor impulsivity, but does not appear to have an effect on working memory or emotional bias [ 138 ]. Lisdexamfetamine is currently the only drug with formal regulatory approval for treating BED.…”
Section: Resultsmentioning
confidence: 99%
“…LDX has been reported to improve inhibitory control in women with binge eating symptoms and, alongside this improvement in cognition, to reduce food intake [ 120 ]. The effects of LDX and other cognitive enhancers on weight loss/prevention of weight gain could be examined in randomized controlled studies [ 121 , 122 ]. Interestingly, ADHD is associated with disinhibited eating and obesity [ 123 , 124 ] and this relationship is related to deficits in attention and cognitive control [ 124 , 125 ].…”
Section: Gaps In Knowledge and Future Directionsmentioning
confidence: 99%
“…Lisdexamfetamine dimesylate (LDX) is currently the only drug approved for the treatment of moderate to severe BED. It is a prodrug of d-amphetamine that significantly reduces intake of highly palatable food ( 4 ), BE frequency, and impulsivity ( 5 , 6 , 7 , 8 ) in people with BED. Despite its demonstrated efficacy in reducing BE episodes, there is speculation whether BED occurs predominantly via altering appetite, reward sensitivity, or cognitive control processes ( 9 ).…”
mentioning
confidence: 99%
“…One study reported reductions in ventromedial prefrontal cortex activation that were correlated with BE symptom reduction after 12 weeks of LDX ( 10 ). The other study reported reduced bilateral thalamic activation after an acute 50 mg dose of LDX administered to 22 women in a randomized, crossover, placebo-controlled design ( 4 ). However, both studies used task-evoked food stimuli designs, which examine LDX-related changes specifically related to the salience of food cues but not across a broader context.…”
mentioning
confidence: 99%